The Success of Communication Goals among Indonesian Learners of Japanese through Communication Strategies - Mael, Masilva Raynox (Studies in Learning and Teaching, 2025)
The use of communication strategies (CS) is crucial when speakers encounter linguistic difficulties in conveying their ideas or intentions to their interlocutors. This study serves as a pilot investigation that lays the foundation for designing instructional approaches to communication strategies. The novelty of this research lies in its focus on integrating CS-based instruction into Japanese conversation teaching for Indonesian learners, an area that has not been previously explored. The types of communication strategies were classified based on the degree of communicative success observed in conversations involving Indonesian learners of Japanese at the basic and intermediate levels. The study employed a cross-case study method, allowing for a systematic comparison between learners at different proficiency levels. Data were collected from one basic-level and one intermediate-level learner, each engaging in a free-topic conversation with a native Japanese speaker for approximately one hour. The findings indicate that the most frequently used communication strategy at the basic level was literal translation, whereas at the intermediate level, the use of fillers was most common. This study represents an initial step toward the development of pedagogical approaches for teaching Japanese communication strategies.